The inverse relationship between fatness and bone mineral content is mediated by the adolescent appendicular skeletal muscle mass index: The Cogni-Action Project - Cristi-Montero, Carlos; Peña-Jorquera, Humberto; Landaeta-Díaz, Leslie; Mello, Julio B.; Araya-Quintanilla, Felipe; Brand, Caroline; Reuter, Cézane; Jorquera, Carlos; Ferrari, Gerson (Frontiers in Nutrition, 2022)
Background Excess adipose tissue negatively influences bone health during childhood, affecting future bone fragility diseases such as osteoporosis. However, little is known about how adolescent appendicular skeletal muscle mass index (ASMI) may mediate the relation between fatness and bone mineral content (BMC). Methods The sample comprised 1,296 adolescents (50% girls) aged 10–14. A principal component analysis was performed to obtain a factor made up of four fatness indicators (a) neck circumference, (b) kilograms of fat, (c) visceral fat area, and (d) waist-to-height ratio. BMC, kilograms of fat, visceral fat area, and appendicular skeletal muscle mass were obtained by a multi-frequency bioelectrical impedance analyzer. ASMI was calculated as the appendicular skeletal muscle mass divided by height squared (kg/m2). A mediation analysis was performed adjusting by age, sex, maturation, socioeconomic status, physical activity, and adolescents' body weight. We also explore differences by sex and nutritional status. Results The fatness factor explained 71.5% of the proportion variance. Fatness was inversely associated with the ASMI and BMC, while the ASMI was positively related to BMC. Overall, the inverse relationship between fatness and BMC was partially mediated by the adolescents' ASMI (29.7%, indirect effect: B= −0.048, 95%CI −0.077 to −0.022), being higher in girls than in boys (32.9 vs. 29.2%). Besides, the mediation effect was higher in adolescents with normal body weight than with overweight-obese (37.6 vs 23.9%, respectively). Conclusions This finding highlighted the relevance of promoting healthy habits to reduce fatness and improve muscle mass in adolescents. Moreover, this highlights the central role of ASMI mediating the inverse association between fatness and BMC in female and male adolescents. Public health strategies should promote bone health in childhood, reducing the incidence of early osteopenia and osteoporosis.